A preparation method for constructing a uniform high-nickel ternary positive electrode material fluoride layer

By directly generating fluorinated layers by using solid phase method on high-nickel ternary positive electrode materials, the problems of cumbersome operation procedures and high production costs in the prior art are solved, and the uniform fluorinated layer construction of the material is achieved, and the circulation performance and thermal stability of the material are improved.

CN119750667APending Publication Date: 2025-04-04JIANGXI GANFENG BATTERY TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411934383.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, when constructing a fluorinated layer of a high nickel ternary cathode material, it is necessary to dissolve the fluorine source in anhydrous organic solvent, and use the solid phase method to generate a uniform fluorinated layer. The operation process is cumbersome and the production cost is high.

Method used

A uniform fluorinated layer is directly generated by the solid phase method. By weighing ammonium fluoride and high-nickel ternary cathode material, it is mixed with low-speed and high-speed under the protection of inert gas, and then heat treatment is performed to form a high-nickel ternary cathode material wrapped in fluorinated layer.

Benefits of technology

The process flow is simplified, production costs are reduced, the uniform distribution of the fluorinated layer is promoted, and the circulation performance and thermal stability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750667A_ABST
    Figure CN119750667A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method for constructing a uniform high-nickel ternary positive electrode material fluoride layer, comprising the following steps: step one: weighing ammonium fluoride solid material and high-nickel ternary positive electrode solid material, putting them into a fusion mixer for low-speed mixing under an inert gas as a protective atmosphere, step two: adjusting the speed of the fusion mixer to high-speed mixing, and making the ammonium fluoride evenly distributed on the surface of the high-nickel ternary positive electrode material through high-speed rotation and vibration, so as to obtain a mixed material A for constructing an ion eutectic coating layer, wherein the inert gas is the protective atmosphere, and step three: adding the mixed material A in the step two into a sintering box body for heat treatment, wherein the heat treatment process is divided into two stages, and a high-nickel ternary positive electrode material wrapped in a fluoride layer is obtained, wherein the mass percentage of lithium fluoride is 0.01-1.0%; the invention directly adopts a solid phase method to generate a uniform fluoride layer, which greatly simplifies the process flow and reduces the cost compared with the wet coating method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and more specifically, to a preparation method for constructing a uniform high-nickel ternary positive electrode material fluoride layer. Background Art

[0002] Lithium-ion batteries have been widely used in various electronic devices due to their advantages of high operating voltage, high energy density and long cycle life. With the advent of the battery era, the energy density requirements for positive electrode materials are getting higher and higher. Therefore, the application of high-nickel ternary positive electrode materials based on lithium nickel cobalt manganese oxide in new energy vehicles is becoming more and more urgent. High-nickel ternary positive electrode materials have the advantages of high specific capacity and low price. However, as energy storage equipment for new energy vehicles, the energy density and cycle life of high-nickel ternary positive electrode materials still need to be improved.

[0003] A Chinese patent publication number CN113764634A disclosed a method for preparing a lithium fluoride in-situ coated high-nickel ternary positive electrode material, which specifically disclosed the following steps: adding a lithium fluoride source to an anhydrous organic solvent, heating and stirring to obtain a solution a; adding the high-nickel ternary positive electrode material to the solution a and stirring to obtain a black suspension b; heating and stirring the suspension b, evaporating the solvent to obtain a high-nickel ternary powder c coated with the lithium fluoride source; heating and keeping the powder c warm to decompose the lithium fluoride source into lithium fluoride in-situ on the surface of the high-nickel ternary positive electrode, to obtain a lithium fluoride in-situ coated high-nickel ternary positive electrode material.

[0004] However, the existing technology requires dissolving the fluorine source in an anhydrous organic solvent, then drying it, and using a solid phase method to generate a uniform fluorinated layer. The operation process is cumbersome, not conducive to industrialization, and has high production costs.

[0005] Therefore, the present application provides a preparation method for constructing a uniform high-nickel ternary positive electrode material fluoride layer to solve the problems existing in the prior art. Summary of the invention

[0006] The purpose and effect of the present invention are achieved by the following specific technical means: A preparation method for constructing a uniform high-nickel ternary positive electrode material fluoride layer comprises the following steps: Step 1: Weigh the ammonium fluoride solid material and the high-nickel ternary positive electrode solid material, put them into a fusion mixer under an inert gas protective atmosphere for low-speed mixing; Step 2: Adjust the speed of the fusion mixer to high-speed mixing, and make the ammonium fluoride evenly distributed on the surface of the high-nickel ternary positive electrode material through high-speed rotation and vibration to obtain a mixed material A for constructing an ion eutectic coating layer, and the inert gas is the protective atmosphere; Step 3: Add the mixed material A in step 2 into a sintering box for heat treatment. The heat treatment process is divided into two stages to obtain a high-nickel ternary positive electrode material wrapped with a fluoride layer, and the mass percentage of lithium fluoride is 0.01~1.0%.

[0007] Preferably, in step 1, the mass ratio of ammonium fluoride to the high-nickel ternary positive electrode material is 1:20-1:200.

[0008] Preferably, the low-speed mixing speed of the fusion mixer in step 1 is 500-800 rpm.

[0009] Preferably, the low speed mixing time in step 1 is 60 to 180 seconds.

[0010] Preferably, the inert gas used in the mixing step 1 is a mixture of one or more of nitrogen, argon and neon.

[0011] Preferably, the high-speed mixing speed of the fusion mixer in step 2 is 2500-3000 rpm.

[0012] Preferably, the high-speed mixing time in step 2 is 60 to 180 seconds.

[0013] Preferably, the inert atmosphere in step 2 is a combination of one or more of nitrogen, argon and neon.

[0014] Preferably, in step three, the temperature of the first heat treatment is 400-500°C, the heating rate of the first heat treatment is 5-10°C / min, the time of the first heat treatment is 10-30min, and the gas flow rate of the inert atmosphere in the first heat treatment is 2-5L / min.

[0015] Preferably, in the step three, the second heat treatment temperature is 150-300° C., the second heat treatment time is 60-180 min, and the gas flow rate of the inert atmosphere in the second heat treatment is 0.5-2 L / min.

[0016] Beneficial effects of the present invention: (1) The present invention directly adopts a solid phase method to generate a uniform fluorinated layer, which greatly simplifies the process flow and reduces costs compared to wet coating.

[0017] (2) The present invention utilizes molten salt to construct an ion eutectic on the surface of the positive electrode particles, so that various ions can be evenly and stably distributed on the surface of the positive electrode material, promoting the subsequent formation of a uniform fluoride layer, thereby better inhibiting irreversible phase change and the dissolution of transition metal ions, and improving the material's cycle performance and thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1This is the TEM image of the fluorinated layer high-nickel ternary positive electrode material constructed in the present invention.

[0019] Figure 2 This is a schematic diagram of the change in static viscosity of the slurry before and after the fluorination layer is constructed for the high-nickel ternary positive electrode material of the present invention.

[0020] Figure 3 This is a cycle performance diagram of the high-nickel ternary positive electrode material of the present invention before and after the fluoride layer is constructed.

[0021] Figure 4 A battery cell with 100% SOC 30D storage at 60°C before and after the fluorination layer is constructed for the high nickel ternary positive electrode material of the present invention DETAILED DESCRIPTION

[0022] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail in the specific embodiments. The following embodiments are only examples of implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the scope of the present invention are all within the scope of patent protection of the present invention.

[0023] Comparative Example 1 NCM9037 is used as the active material, and CNT, SP, and binder are made into cathode slurry in a ratio of 97:0.5:1:1.5. The cathode electrode sheet is formed by coating roller pressing, and the graphite negative electrode is the counter electrode. The N / P ratio is 1.13, and the winding process is used to form a 3.5Ah small soft pack battery cell; The cathode slurry viscosity was tested using a rotational viscometer, and the test times were 0h, 2h, 4h, 6h, 8h, 10h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h, 60h, and 72h.

[0024] The volume of the battery cells before and after storage was tested using the water displacement method; A blue electric tester was used for constant current charge and discharge tests, the test temperature was 25℃±2℃, the charge and discharge cut-off voltage was 3.0-4.3V, and the cycle rate was 1C. Example 1

[0025] The present invention provides a method for constructing a uniform high-nickel ternary positive electrode material fluoride layer, comprising the following steps: The unmodified high-nickel ternary cathode material used is the commercially available NCM9037 high-nickel ternary cathode material (LiNi0.9Co0.03Mn0.07O2). Under the condition of dew point ≤-35°C, 0.2kg of ammonium fluoride and 10kg of NCM9037 were weighed and added to the fusion mixer. High-purity nitrogen was used as the protective gas. The low speed of the mixer was 600rpm, the duration was 120s, and the high speed of the mixer was 2600rpm, the duration was 150s, and the mixed material A for constructing the ion eutectic coating layer was obtained. Material A was transferred to the sintering box for heat treatment. High-purity nitrogen was used as the protective gas. It was kept warm at 460°C for 10min, the heating rate was 5°C / min, and the gas flow rate was 4L / min. Then the temperature was lowered to 260°C and kept for 120 min at a gas flow rate of 1 L / min. After the heat treatment, it was cooled to room temperature to obtain a high-nickel ternary positive electrode material F-NCM9037-1 with a uniform fluoride layer. Example 2

[0026] Under the condition of dew point ≤-35℃, weigh 0.05kg ammonium fluoride and 10kg NCM9037, add them to the fusion mixer, use high-purity nitrogen as protective gas, mix at a low speed of 800rpm, last for 90s, mix at a high speed of 2800rpm, last for 180s, and obtain mixed material A for constructing ion eutectic coating layer. Transfer material A to the sintering box for heat treatment, use high-purity nitrogen as protective gas, keep warm at 500℃ for 5min, heating rate of 10℃ / min, gas flow rate of 5L / min. Then cool to 300℃ and keep warm for 60min, gas flow rate of 2L / min. After the heat treatment, cool to room temperature to obtain high nickel ternary positive electrode material F-NCM9037-2 with uniform fluoride layer. Example 3

[0027] Under the condition of dew point ≤-35℃, 0.1kg ammonium fluoride and 10kg NCM9037 were weighed and added to the fusion mixer. High-purity nitrogen was used as the protective gas. The low speed of the mixer was 500rpm, the duration was 150s, and the high speed of the mixer was 3000rpm, the duration was 120s, and the mixed material A for constructing the ion eutectic coating layer was obtained. Material A was transferred to the sintering box for heat treatment. High-purity nitrogen was used as the protective gas. The temperature was kept at 420℃ for 8min, the heating rate was 8℃ / min, and the gas flow rate was 3L / min. Then the temperature was lowered to 200℃ and kept for 120min, the gas flow rate was 0.5L / min, and after the heat treatment, it was cooled to room temperature to obtain F-NCM9037-3 with a uniform fluoride layer. Example 4

[0028] Under the condition of dew point ≤-35℃, 0.5kg ammonium fluoride and 10kg NCM9037 were weighed and added to the fusion mixer, high-purity nitrogen was used as the protective gas, the low speed of the mixer was 700rpm, the duration was 60s, and the high speed of the mixer was 2900rpm, the duration was 180s, and the mixed material A for constructing the ion eutectic coating layer was obtained. Material A was transferred to the sintering box for heat treatment, high-purity nitrogen was used as the protective gas, and the temperature was kept at 480℃ for 10min, the heating rate was 5℃ / min, and the gas flow rate was 3L / min. Then the temperature was lowered to 150℃ and kept for 120min, the gas flow rate was 1.5L / min, and after the heat treatment, it was cooled to room temperature to obtain F-NCM9037-4 with a uniform fluoride layer. Example 5

[0029] Under the condition of dew point ≤-35℃, 0.2kg ammonium fluoride and 10kg NCM9037 high nickel ternary positive electrode material were weighed and added to the fusion mixer. The low speed of the mixer was 800rpm, the duration was 120s, and the high speed of the mixer was 2700rpm, the duration was 150s, and the mixed material A for constructing the ion eutectic coating layer was obtained. Material A was transferred to the sintering box for heat treatment, with high-purity nitrogen as the protective gas, and kept at 400℃ for 10min, the heating rate was 6℃ / min, and the gas flow rate was 4L / min. Then the temperature was lowered to 200℃ and kept for 120min, the gas flow rate was 1L / min, and after the heat treatment, it was cooled to room temperature to obtain the high nickel ternary positive electrode material F-NCM9037-5 with a uniform fluoride layer.

[0030] Figure 1 This is the TEM after coating with lithium fluoride layer. It can be seen from the figure that lithium fluoride is densely, evenly and stably coated on the surface of positive electrode particles.

[0031] Figure 2 Comparison of static viscosity of cathode slurry prepared by NCM9037 and F-NCM9037-1. After 72 hours of static, the viscosity of cathode slurry of NCM9037 rises to 48100mPa.s, and the viscosity of cathode slurry of F-NCM9037-1 is 16200mPa.s. The slurry stability of the material is significantly enhanced after the fluorination layer is constructed. This is because the construction of the fluorination layer consumes the residual alkali on the surface of the material and inhibits the reaction between -OH and PVDF molecular chain.

[0032] Figure 3The battery cells prepared for NCM9037 and F-NCM9037-5 are compared in terms of their state after storage at 60°C 100% SOC for 30 days. The NCM9037 battery cells show obvious bloating, with a volume expansion rate of 120.65%, while the volume expansion rate of F-NCM9037-5 is only 11.37%. The storage performance of the material is significantly improved after the fluoride layer is constructed, which indicates that the fluoride layer can effectively prevent the contact between the electrolyte and the cathode material and inhibit the release of lattice oxygen in the material.

[0033] Figure 4 The capacity retention rate of the battery cells prepared for NCM9037 and F-NCM9037-5 at 25℃ 3.0~4.3V 1C / 1C. The capacity retention rate of NCM9037 decays to 80% after 600cls of cycling, while the capacity retention rate of F-NCM9037-5 is still 90% after 1000cls of cycling.

[0034] Table 1 shows the change in static viscosity of the cathode slurry after different preparation processes for 72 hours, the cell expansion rate at 60°C 100% SOC for 30 days, and the capacity retention rate at 25°C 3.0~4.3V 1C / 1C.

[0035] Group Cathode slurry 72h static viscosity mPa.s 60℃100%SOC30 days Cell volume expansion rate 3.0-4.3V1C Capacity retention rate Group Cathode slurry 72h static viscosity mPa.s 60℃100%SOC30days battery cell volume expansion rate 3.0-4.3V 1C capacity retention rate Comparative Example 1 48100 120.65% 600cls@80% Example 1 16200 12.64% 1000cls@88% Example 2 36700 9.21% 1000cls@87% Example 3 34500 10.12% 1000cls@89% Example 4 26500 12.21% 1000cls@88% Example 5 24800 11.37% 1000cls@90% The above results show that after the fluorinated layer is constructed on the NCM9037 material, the processability of the material is improved, the side reaction between the material and the electrolyte is inhibited, the high-temperature storage performance and cycle performance of the material are improved, and the electrochemical properties of the material are improved.

[0036] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a uniform high-nickel ternary cathode material fluoride layer, characterized in that: The following steps are involved: Step 1: Weigh the ammonium fluoride solid material and the high-nickel ternary positive electrode solid material, put them into a fusion mixer under an inert gas protective atmosphere for low-speed mixing; Step 2: Adjust the speed of the fusion mixer to high-speed mixing, and make the ammonium fluoride evenly distributed on the surface of the high-nickel ternary positive electrode material through high-speed rotation and vibration to obtain a mixed material A for constructing an ion eutectic coating layer, and the inert gas is the protective atmosphere; Step 3: Add the mixed material A in step 2 into a sintering box for heat treatment. The heat treatment process is divided into two stages to obtain a high-nickel ternary positive electrode material wrapped with a fluoride layer, and the mass percentage of lithium fluoride is 0.01~1.0%.

2. A method for preparing a uniform high-nickel ternary positive electrode material fluoride layer according to claim 1, characterized in that: In the step 1, the mass ratio of ammonium fluoride to the high-nickel ternary positive electrode material is 1:20-1:

200.

3. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: The low speed mixing speed of the fusion mixer in step 1 is 500-800 rpm.

4. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: The low speed mixing time in step 1 is 60 to 180 seconds.

5. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: The inert gas used in the mixing step 1 is a mixture of one or more of nitrogen, argon and neon.

6. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: The high-speed mixing speed of the fusion mixer in step 2 is 2500-3000 rpm.

7. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: The high-speed mixing time in step 2 is 60 to 180 seconds.

8. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: The inert atmosphere in step 2 is a combination of one or more of nitrogen, argon and neon.

9. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: In the step three, the temperature of the first heat treatment is 400-500°C, the heating rate of the first heat treatment is 5-10°C / min, the time of the first heat treatment is 10-30min, and the gas flow rate of the inert atmosphere in the first heat treatment is 2-5L / min.

10. The method for preparing a uniform high-nickel ternary cathode material fluoride layer according to claim 1, characterized in that: In the step three, the second heat treatment temperature is 150-300° C., the second heat treatment time is 60-180 min, and the gas flow rate of the inert atmosphere in the second heat treatment is 0.5-2 L / min.

Citation Information

Patent Citations

  • Preparation method of lithium fluoride in-situ coated high-nickel ternary positive electrode material

    CN113764634A